Peran Agen Asuransi di Era Digital dalam Pemasaran Produk Asuransi - Muhammad Fauzan; Maryam Batubara (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
This article will discuss the impact of technological advances on the insurance industry. Digital insurance is a type of insurance that can be purchased online, which makes it easier to obtain insurance without using an intermediary. All previously traditional insurance purchasing processes can now be completed online at any time and from any location as long as you have an internet connection. Nowadays, various digital insurance options are also accessible, including online life insurance offered by insurance companies, travel insurance, car insurance, health insurance, and accident insurance. Apart from being purchased online, buyers will receive their insurance policy in digital format, which is usually called an electronic policy. Usually, online insurance policies. The claim procedure can also be completed online. When compared to traditional insurance promoted by marketers, digital insurance is generally not much different. For those of you who want to start trying to get protection, digital insurance offers a number of benefits that are worth considering.